2021
DOI: 10.1186/s12967-021-02787-5
|View full text |Cite
|
Sign up to set email alerts
|

CMTM6 promotes migration, invasion, and EMT by interacting with and stabilizing vimentin in hepatocellular carcinoma cells

Abstract: Background CKLF like MARVEL transmembrane domain containing 6 (CMTM6) has been associated with the development in many kinds of cancers. However, the roles of CMTM6 in hepatocellular carcinoma (HCC) are largely unknown. Thus, the present study aimed to investigate the function of CMTM6 in HCC. Methods We analysed CMTM6 levels and functions using human HCC cell lines, paired HCC and adjacent non-tumorous tissues, and a tissue microarray. CMTM6 expre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“… 12–14 Meanwhile, CMTM6 promotes cell migration and invasion by enhancing EMT progression, a fundamental mechanism for the metastatic phenotype of malignant tumors. 13 , 30 In our study, we found that CMTM6 was overexpressed in ccRCC tissues and was significantly associated with advanced tumor grade, early lymph node and distant metastases, and adverse prognosis. Interestingly, HKC cells, a commonly used human renal tubular epithelial cell line with characteristics of being immortalized, expressed similar level of CMTM6 in comparison with that in most of ccRCC cell lines ( Figure 2a ).…”
Section: Discussionmentioning
confidence: 58%
“… 12–14 Meanwhile, CMTM6 promotes cell migration and invasion by enhancing EMT progression, a fundamental mechanism for the metastatic phenotype of malignant tumors. 13 , 30 In our study, we found that CMTM6 was overexpressed in ccRCC tissues and was significantly associated with advanced tumor grade, early lymph node and distant metastases, and adverse prognosis. Interestingly, HKC cells, a commonly used human renal tubular epithelial cell line with characteristics of being immortalized, expressed similar level of CMTM6 in comparison with that in most of ccRCC cell lines ( Figure 2a ).…”
Section: Discussionmentioning
confidence: 58%
“… 58 , 59 Furthermore, the upregulated CMTM4 expression in HCC facilitates escaping from antitumor T-cell immunity and contributes to an immunosuppressive tumor microenvironment. 59 Similar to CMTM4, CMTM6 expression was downregulated 78 or upregulated 80 , 110 in HCC tissues. The reasons for the contradiction between these studies are still ambiguous; however, small-scale specimens, heterogeneity of tumor tissue, and observational bias are possible factors.…”
Section: Cmtm Family Members In Digestive System Cancersmentioning
confidence: 97%
“…Recent studies have shown that CMTM6 expression is upregulated in HCC tissues, and its overexpression increases cell proliferation and enhances cell invasion and migration and induces epithelial–mesenchymal transition (EMT) mechanistically by stabilizing vimentin. 80 In addition, the co-expression of CMTM6/PD-L1 can regulate inflammatory cell density 77 and has a close relationship with tumor recurrence. 81 Given the participation of CMTM6 in PD-L1 stabilization, 9 , 10 combined treatment with anti-CMTM6 and anti-PD-L1 may be a new method to enhance the therapeutic benefits in HCC.…”
Section: Cmtm Family Members In Digestive System Cancersmentioning
confidence: 99%
“…CMTM6 and CMTM4 can affect tumor proliferation, metastasis, maintain the tumor stem cells phenotypes and promote epithelial-mesenchymal transition (EMT). CMTM6 promoted tumor proliferation, migration, and invasion in various tumors, such as RCC ( 27 ), gliomas ( 19 ), and HCC ( 105 ). Wei et al.…”
Section: The Expression Of Cmtm6/4 Is Associated With the Immune-rela...mentioning
confidence: 99%
“…EMT-induced epithelial plasticity could be manifested by changes in the expression of epithelial markers including E-cadherin and mesenchymal proteins including N-cadherin and vimentin ( 113 ). Recent study demonstrated that CMTM6 induces EMT by stabilizing vimentin, which in turn promote migration and invasion of tumor cells in HCC ( 105 ). The effect of CMTM6 on EMT may be mediated through Wnt/β-catenin signaling ( 18 ).…”
Section: The Expression Of Cmtm6/4 Is Associated With the Immune-rela...mentioning
confidence: 99%